Strategies to Develop Earth‐Abundant Heterogeneous Oxygen Evolution Reaction Catalysts for pH‐Neutral or pH‐Near‐Neutral Electrolytes. Issue 1 (3rd November 2020) - Dong, Yan; Komarneni, Sridhar
Abstract: The anodic oxygen evolution reaction (OER) is the bottleneck of water splitting to produce hydrogen due to its sluggish kinetics. In order to lower the energy cost, highly active and cost‐efficient OER catalysts need to be used to overcome the OER reaction barrier, especially in neutral pH. Compared to alkaline or acidic electrolytes, pH‐neutral or pH‐near‐neutral electrolytes are considered to be cheaper and safer, and water from rivers and the sea could be used directly under such conditions. However, OER under neutral pH is challenging compared to the OER catalysts for alkaline conditions. Therefore, OER catalysts for neutral or near‐neutral pH have not been pursued significantly and, hence, there are limited advances in this area. Here, the progress made in the research and development of earth‐abundant heterogeneous catalysts for OER in three pH‐neutral or pH‐near‐neutral systems, namely, the phosphate system, the carbonate system, and the borate system, are systematically reviewed and summarized for the first time. Strategies to develop high‐performance OER catalysts for neutral pH are reviewed and summarized. In addition, future challenges and opportunities in this field are discussed, which may shed some light on the future developments of earth‐abundant heterogeneous catalysts for OER in neutral or near‐neutral pH. Abstract : In this paper, strategies to develop high‐performance oxygen evolution reaction (OER) catalysts for three major OER systems under neutral or near‐neutral pH, namely, the phosphate system, the carbonate system, and the borate system, are reviewed. Methods to develop such types of catalysts are summarized. Challenges and research opportunities in this field are also discussed.